Reperfusion mediates heme impairment with increased protein cysteine sulfonation of mitochondrial complex III in the post-ischemic heart. (December 2021) - Chen, Chwen-Lih; Kang, Patrick T.; Zhang, Liwen; Xiao, Kunhong; Zweier, Jay L.; Chilian, William M.; Chen, Yeong-Renn
Abstract: A serious consequence of myocardial ischemia-reperfusion injury (I/R) is oxidative damage, which causes mitochondrial dysfunction. The cascading ROS can propagate and potentially induce heme bleaching and protein cysteine sulfonation (PrSO3 H) of the mitochondrial electron transport chain. Herein we studied the mechanism of I/R-mediated irreversible oxidative injury of complex III in mitochondria from rat hearts subjected to 30-min of ischemia and 24-h of reperfusion in vivo. In the I/R region, the catalytic activity of complex III was significantly impaired. Spectroscopic analysis indicated that I/R mediated the destruction of hemes b and c + c 1 in the mitochondria, supporting I/R-mediated complex III impairment. However, no significant impairment of complex III activity and heme damage were observed in mitochondria from the risk region of rat hearts subjected only to 30-min ischemia, despite a decreased state 3 respiration. In the I/R mitochondria, carbamidomethylated C122 /C125 of cytochrome c 1 via alkylating complex III with a down regulation of HCCS was exclusively detected, supporting I/R-mediated thioether defect of heme c 1 . LC-MS/MS analysis showed that I/R mitochondria had intensely increased complex III PrSO3 H levels at the C236 ligand of the [2Fe2S] cluster of the Rieske iron‑sulfur protein ( uqcrfs1 ), thus impairing the electron transport activity. MS analysis also indicated increased PrSO3 H of the hinge protein at C65 and of cytochrome c 1 at C140 and C220, which are confined in the intermembrane space. MS analysis also showed that I/R extensively enhanced the PrSO3 H of the core 1 ( uqcrc1 ) and core 2 ( uqcrc2 ) subunits in the matrix compartment, thus supporting the conclusion that complex III releases ROS to both sides of the inner membrane during reperfusion. Analysis of ischemic mitochondria indicated a modest reduction from the basal level of complex III PrSO3 H detected in the mitochondria of sham control hearts, suggesting that the physiologic hyperoxygenation and ROS overproduction during reperfusion mediated the enhancement of complex III PrSO3 H. In conclusion, reperfusion-mediated heme damage with increased PrSO3 H controls oxidative injury to complex III and aggravates mitochondrial dysfunction in the post-ischemic heart . Graphical abstract: Unlabelled Image Highlights: I/R propagates heme damage and sulfonation of complex III and adds insult to mitochondrial injury. Reperfusion mediates heme c1 damage with thioether bonds defect. Cysteine sulfonation of C236 ligand in RISP impairs electron transfer activity. Heme damage and cysteine sulfonation predisposes myocardial redox setting more oxidized. Heme damage and cysteine sulfonation enhances superoxide production in mitochondria.